ERROR ANALYSIS OF STUDENTS’ PRONUNCIATION IN PRONOUNCING ENGLISH VOWEL AT THE FIRST SEMESTER IN ENGLISH DEPARTMENT OF UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Novra Melisa P. Hutabarat (Sean Institute, 2023)
This study deals with the pronouncing English words of the first semester students in English Study Program of University of HKBP Nommensen Pematangsiantar. The objective of this study were to find out the types of pronunciation errors on vowels were made by the first semester students and the errors did to the first semester students in English Department of University of HKBP Nommensen Pematangsiantar. The scope of the research was focuses on types pronunciation error by Dulay et al based on Surface Strategy Taxonomy, they were error of omission, addition error, misinformation error, and misordering error. The researcher limited this research only focuses on error analysis of students’ pronunciation in pronuncing English vowel. The result of analyzing data showed that the total number of all errors in students’ pronunciation error is 17 errors. The researcher found the 3 errors of ommision i.e. 18%, 4 errors of addition i.e. 23%, 9 errors of misformation i.e. 53%, and 1 errors of misordering i.e. 6%